A conceptual introduction to academic guidance in universities - LAICHE, Samiha; HMAIDI, Messaouda (Social Sciences Journal, 2021)
The purpose of this study is to identify academic guidance in universities, which is an important educational and administrative service to support the educational process of universities through which Students who encounter difficulties in their educational career, in this regard, we attempt to provide a comprehensive overview, highlighting the most important concepts by referring to some definitions, objectives and types, as well as some models of foreign and Arab universities.